Exosomes Isolated From Bone Marrow Mesenchymal Stem Cells Exert a Protective Effect on Osteoarthritis via lncRNA LYRM4-AS1-GRPR-miR-6515-5p - Wang, Xiuhui; Li, Zhuokai; Cui, Yin; Cui, Xu; Chen, Cheng; Wang, Zhe (Frontiers in Cell and Developmental Biology, 2021)
Objectives The aim of this study was to investigate the effects of exosomes isolated from human bone marrow mesenchymal stem cells (BMSCs) on osteoarthritis (OA) and a competitive endogenous RNA (ceRNA) network. Methods Exosomes were isolated from human BMSCs and characterized by transmission electron microscopy (TEM), Nanosight (NTA), and western blotting. Chondrocytes were treated with interleukin-1β (IL-1β) and then transfected with exosomes. Cell viability and apoptosis were determined using Cell Counting Kit-8 (CCK-8) and flow cytometry, respectively. Cells with IL-1β and exosomes were sequenced, and differentially expressed lncRNAs (DE-lncRNAs) and miRNAs (DE-miRNAs) were identified. Thereafter, a ceRNA network (LYRM4-AS1-GRPR-miR-6515-5p) was chosen for further validation. Results TEM, NTA, and western blotting showed that exosomes were successfully isolated, and PKH67 staining showed that exosomes could be taken up by IL-1β-induced chondrocytes. Compared with the control group, IL-1β significantly decreased cell viability and promoted apoptosis (P < 0.05), while exosomes reversed the changes induced by IL-1β. For MMP3, AKT, and GRPR, IL-1β upregulated their expression, while exosomes downregulated their expression. For PTEN, there was no significant difference in PTEN expression between the control and IL-1β groups; however, exosomes markedly upregulated PTEN expression. By sequencing, 907 DE-lncRNAs and 25 DE-miRNAs were identified, and a ceRNA network was constructed. The dual-luciferase reporter gene indicated that LYRM4-AS1, miR-6515-5, and GRPR interacted with each other. The results of cell experiments showed that LYRM4-AS1 regulated the growth of IL-1β-induced chondrocytes by GRPR/miR-6515-5p. Conclusion Exosomes may alleviate OA inflammation by regulating the LYRM4-AS1/GRPR/miR-6515-5p signaling pathway.